EVALUATING BLOOD PRESSURE AND COGNITIVE IMPAIRMENT IN URBAN ELDERLY - Kuldeep Dineshbhai Varmora; Brijesh Ketankumar Lakhani; Kalola Akshaybhai Ramjibhai; Chadamiya Uttam Dineshbha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: With rising life expectancy, cognitive dysfunction has emerged as a growing health concern among the elderly, especially in urban populations. Blood pressure, a critical modifiable risk factor, is increasingly being linked to cognitive decline. However, limited data exist on its correlation with cognitive function in the urban elderly population in India.Aim: To assess the correlation between blood pressure and cognitive function as measured by the Mini Mental State Examination (MMSE) in the urban elderly population.Materials and Methods: This cross-sectional study included 370 urban elderly individuals aged ≥60 years. Blood pressure was recorded using a digital sphygmomanometer, and cognitive status was assessed with the MMSE tool. Participants were categorized into two groups based on MMSE scores (>23 vs. ≤23). Statistical analysis was conducted using SPSS version 26, and the correlation between blood pressure and cognitive scores was evaluated using Pearson’s correlation coefficient.Results: The mean age of the study population was 71.26 ± 8.43 years. Participants with MMSE scores ≤23 showed significantly higher mean systolic blood pressure (143.72 ± 17.62 mmHg) compared to those with MMSE >23 (137.89 ± 15.94 mmHg, p = 0.042). Diastolic pressure was also significantly lower in cognitively impaired individuals (81.27 ± 10.14 mmHg vs. 85.64 ± 9.85 mmHg, p = 0.036). These findings indicate a significant inverse relationship between blood pressure abnormalities and cognitive function.Conclusion: The study highlights a statistically significant association between abnormal blood pressure—particularly elevated systolic and lower diastolic pressure—and cognitive impairment in urban elderly individuals. These results underscore the importance of routine cognitive screening and optimal blood pressure control in elderly care.